Evidence-Based Practice with Emotionally Troubled Children and Adolescents - Glicken, Morley (Elsevier, 2011)
At a time when increasing numbers of children are being treated for emotional problems, naming and treating those problems remains more of an art than a science often leaving children and their parents to navigate a confusing path.